2009
DOI: 10.1007/s00203-009-0510-y
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a Clostridium perfringens type D epsilon toxin producer via dot-blot test

Abstract: Clostridium perfringens type D produces enterotoxemia, an enteric disease in ruminants, also known as pulpy kidney disease. Caused by epsilon toxin, enterotoxemia is a major exotoxin produced by this microorganism. Epsilon toxin is also the main component of vaccines against this enteric disorder. In this study, a standardized dot-blot was used to choose strains of C. perfringens type D that are producers of epsilon toxin. Clones producing epsilon toxin were chosen by limiting dilution; after three passages, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The production of vaccines that can protect against Clostridium spp. has been continually reported as problematic due to factors related to the culture of these pathogenic microorganisms and how they behave under anaerobic conditions 13 14 15 . The process used in this work involved simpler procedures and materials than those used to develop commercial vaccines, and, therefore, has the potential to overcome most of the problems related to the industrial scale production of such vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of vaccines that can protect against Clostridium spp. has been continually reported as problematic due to factors related to the culture of these pathogenic microorganisms and how they behave under anaerobic conditions 13 14 15 . The process used in this work involved simpler procedures and materials than those used to develop commercial vaccines, and, therefore, has the potential to overcome most of the problems related to the industrial scale production of such vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Since conventional vaccines do not rely on direct quantification of antigens, but on their ability to generate protective antibodies, a large batch-to-batch variation in the number of doses produced is likely to occur 3 13 . Thus, the use of recombinant antigens offers the possibility of overcoming this problem, once they can be easily quantified and related to the protective levels generated in animals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported many problems with commercial enterotoxemia vaccines, such as the difference in antigen concentration and potency of the vaccine from batch to batch which cause inequality of antigen concentration distributed in each injection vial [ 8 , 11 , 15 , 16 ] so that potency of the vaccine varies from batch to batch [ 9 , 10 , 17 ]. In order to detect and measure the C. perfringens epsilon toxoid in each batch, and evaluatethe immunogenicity of vaccines prepared, we developed an ETX sandwich ELISA test using specific recombinant antibodies against pure C. perfringens epsilon toxoid.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported many problems with commercial enterotoxemia vaccines, such as the difference in antigen concentration and potency of the vaccine from batch to batch which cause inequality of antigen concentration distributed in each injection vial [8,11,15,16] so that potency of the vaccine varies from batch to batch [9,10,17]. In order to detect and measure the C. perfringens epsilon toxoid in each batch, and evaluatethe immunogenicity of vaccines prepared, we developed an ETX sandwich ELISA test using speci c recombinant antibodies against pure C. perfringens epsilon toxoid.…”
Section: Discussionmentioning
confidence: 99%